The Role of Institutional Quality in a Currency Crisis Model - Wu, Yi (International Monetary Fund, 2008)
This paper is a theoretical study of the impact of institutional quality on currency crises from a public finance point of view. Recent empirical studies leave little doubt that weak institutions, including high levels of corruption, hinder economic performance. After the East Asian crisis, many observers have pointed to widespread corruption and crony capitalism as an underlying cause. Despite the popularity of the claim, there are only limited empirical and especially theoretical studies on the link between institutional quality and currency crises. This paper intends to fill in this void. We model institutional weakness as an inefficiency of the tax collection system. The model derived here shows that institutional weakness generally increases the likelihood of the existence of a self-fulfilling crisis equilibrium, and leads to larger currency devaluation when crises happen. However, this relationship could reverse when institutional weakness is very severe.